Productive Word-Forming Models of Surnames in Dialect Speech: Suffix Derivatives, Their Contextual Appearances and Historical Interpretation - Shulska, Nataliia; Kostusiak, Nataliia; Kostusiak, Dmytro; Zinchuk, Ruslana; Rudianyn, Ivan; Vilchynska, Tetiana; Bachynska, Halyna; Verbovetska, Oksana; Svystun, Nina; Savchyn, Tetyana (My University, 2024)
The article presents an analysis of productive word-formation models of Western Polissia nicknames that function in dialect speech. Substantive and attributive types of masculine and feminine suffix derivatives are characterized in detail in the contextual and historical dimension, attention is paid to word-formation models with the meaning of collectiveness. The material of the research was the own records of nicknames made in the settlements of Western Polissia. The interdependence of the nickname and the colloquialism in which it functions is noted, since unofficial anthroponyms clearly demonstrate dialectal features at the phonetic, lexical, and word- forming levels. Street personal names cannot be brought closer to the framework of the literary language, because their main properties will be lost: changeability, variability, temporality, locativeness, expressiveness, which distinguish them among other anthroponymic units. It has been established that in nicknames, as in last names, only suffixation is evidenced among the means of morphological word formation, because prefix derivatives were found even at the level of formation of appellatives. A comprehensive analysis of suffix formants in Western Polissia unofficial anthroponymy has shown their following varieties: 1) patronymic and matronymic; 2) patronymic-possessive and matronymic-possessive; 3) multifunctional in the sense of patronymic or matronymic; 4) andronymous; 5) collective.
Keywords: nickname; word formation model; Western Polissia dialect; suffix derivative; saying; sentence; scientific paradigm; historical interpretation